Macrophyte banks and fish early stages in a cascade of small hydropower reservoirs (south-eastern Brazil): temporal changes along the reproductive cycle and influence of the limnological and spatial organisation - Kimura, Rafaela Shizuko Yamashita [UNESP]; Brambilla, Eduardo Meneguzzi [UNESP]; Nogueira, Marcos Gomes [UNESP] (Csiro Publishing, 2024)
Context Small hydroelectric power plants (SHPs) are worldwide-distributed infrastructures, the ecological impacts of which are still poorly known.Aim To evaluate the role of littoral macrophytes as nursery areas for fishes in a cascade of three SHP reservoirs in south-eastern Brazil.Methods Three random macrophyte banks, from the intermediate and lentic compartments of each reservoir, were sampled (with manual sieves and gillnets) monthly along the peak of the reproductive period. Basic limnological variables were simultaneously measured.Key results In all, 88 larvae and 393 juveniles were captured, corresponding to 29 taxa, constituting almost 30% of the regional pool of fishes in the river. Non-migrants and short-distance migrants (with or without parental care) predominated. The species accumulation curve tended to an asymptotic configuration (whole dataset sampling effort). Fish abundance differed, mainly temporally, and, at a lower degree, spatially. Higher diversity (rarefaction and extrapolation curves) occurred both at the beginning of the reproductive peak and in the first (upstream) reservoir, where there was also a good correspondence between observed and estimated richness, i.e. 90%.Conclusions The macrophyte banks in these SHP reservoirs are effectively used as nursery areas.Implications Results have provided important insights for actions of conservation and management of the local and regional ichthyofauna, in a condition where typical nursery areas do not exist.
Keywords: ichthyofauna; juveniles; larvae; macrophyte; nursery areas; reproductive strategies; reservoir cascade; Sapuca & iacute;-Mirim River